A Comparative Study of the Effectiveness of Art Therapy and Play Therapy in Developing Cognitive Abilities among Preschool Children with a History of Stunting - Yusnika Damayanti; Devi Annisa Marpaung (JURNAL KESMAS DAN GIZI (JKG), 2025)
Stunting is a serious nutritional problem that adversely affects children's physical and cognitive development. This study aimed to compare the effectiveness of Art Therapy and Play Therapy in enhancing cognitive abilities of preschool-aged children with a history of stunting in the Lawe Sumur Public Health Center working area. A quasi-experimental design with a control group was employed involving 80 preschool children randomly assigned to either the Art Therapy group (n = 40) or the Play Therapy group (n = 40). The intervention consisted of 12 sessions over six weeks, and cognitive abilities were assessed using the Preschool Cognitive Ability Scale (SKKP-15) before and after the intervention. Results indicated that Art Therapy was more effective than Play Therapy in improving cognitive abilities. Children receiving Art Therapy were 3.4 times more likely to achieve high cognitive ability compared to those receiving Play Therapy (p = 0.02; OR = 3.444; 95% CI: 1.310–9.058). Family environment factors, including maternal education level, employment status, family size, frequency of home stimulation, and quality of sleep, also influenced cognitive development. Nonetheless, Art Therapy consistently produced positive effects, even for children from families with limited stimulation and lower parental education. In conclusion, Art Therapy is an effective, practical, and inclusive non-pharmacological intervention for supporting the cognitive development of preschool children with a history of stunting. These findings provide a basis for health professionals, educators, and policymakers to integrate arts-based approaches into child development intervention programs in community health settings.